Weight Change for Pediatric Completers in a National Weight Loss Program - Rochelle Cason-Wilkerson MD, MPH; Darcy Thompson MD, MPH; Nia Mitchell MD, MPH (SAGE Publishing, 2021)
Overweight and obese children in low-income households have limited access to weight loss programs. Low-cost programs should be evaluated in this population. The objective of the current study is to determine weight change among 7 to 17-year-old participants in Take Off Pounds Sensibly (TOPS), a national, low-cost weight loss program. This nonconcurrent prospective study analyzes the cumulative change in weight z -score for overweight and obese children and adolescents who joined TOPS from 2008 to 2011 and consecutively renewed their annual membership. The study includes 586 individuals. At 1-year, cumulative mean (SD) weight z -score change was −0.13 (31). In general, mean change in weight z -scores was no different in subsequent years. Mean weight z -score of children and adolescent TOPS participants who renew their program membership decreased significantly in the first year. Randomized controlled trials should prospectively evaluate this program in children and adolescents.